Career development and unemployment problems in Malaysia crisis of education and training - Abd. Rahim Abd. Rashid; Sufean Hussin; Abu Talib Putih (Siri pengajian dan pendidikan Utusan, 2005)
This book explores the key issues and problems pertaining to career development and unemployment problems that currently undersiege the hopes of Malaysian graduates.